The Role of Sharia Banks as Nazhir Partners in the Management of CWLS Retail SWR001 Investment Products - Dian Lailatullailia; Arin Setiyowati; Abdul Wahab (Perisai : Islamic Banking and Finance Journal, 2021)
Islamic social finance, one of which waqf should have a position and role that can synergize to contribute economically, considering Indonesia has the largest Muslim population in the world. The issue that the potential waqf assets of 2000 trillion with about 51,155.57 ha of waqf land that exists today has not been a productive asset that serves as a source of income in developing the people's economy. While the potential of cash waqf that reaches Rp 180 trillion (BWI) but collected around 391 billion. Therefore, needs the innovation of social finance-based investment scheme with the support of professionalization in its management (in this case nadzir board), one of which is LKS-PWU, especially Sharia Banking. Through State Sukuk instruments in the form of CWLS retail SWR001 products, the government and BWI involve Sharia Banking as Nazhir partners and distribution partners. This study aims to explain the role of sharia banking as nazhir partners in the management of Cash Waqf Linked Sukuk (CWLS) retail SWR001 investment products in the perspective of the basic principles of waqf. This research was conducted by qualitative research method, Library Research approach. Validity of data with source triangulation. The data analysis technique in this study is to use discourse analysis. The results showed that Policy, management and technical processes conducted by Sharia Banking in the management of CWLS Retail SWR001 both in terms of nazhir criteria, the process of collecting and distributing waqf funds is compatibility with the provisions of the Basic Principles of Waqf (PPW) at points 13, 15 and 17 in order to realize good governance for nazhir(Good Nazhir Governance). Keywords: Islamic Bank, Cash Waqf, CWLS Retail SWR001, Waqf Core Priciples (WCP), Good Nazhir Governance